2017
DOI: 10.1128/mbio.00713-17
|View full text |Cite
|
Sign up to set email alerts
|

Viral DNA Replication Orientation and hnRNPs Regulate Transcription of the Human Papillomavirus 18 Late Promoter

Abstract: The life cycle of human papillomaviruses (HPVs) is tightly linked to keratinocyte differentiation. Although expression of viral early genes is initiated immediately upon virus infection of undifferentiated basal cells, viral DNA amplification and late gene expression occur only in the mid to upper strata of the keratinocytes undergoing terminal differentiation. In this report, we show that the relative activity of HPV18 TATA-less late promoter P811 depends on its orientation relative to that of the origin (Ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…RNA virus: YFV 350 Immunity modulation RNA virus: HFDV 354 Cellular transformation DNA virus: HBV, [363][364][365][366] Small chaperone Hsp27 Viral replication RNA virus: EV-A71, 384 Swine fever virus (CSFV), 388 Porcine epidemic diarrhoea virus (PEDV) 389 DNA virus: Adenovirus, 390 HSV-1, 397 Virus entry and uncoating RNA virus: Newcastle disease Virus, 402 DEGV [402][403][404] DNA virus: SV40 413 RT virus: HIV 407,410 Virus translation RNA virus: EV-A71 415 Oxidative stress and ER stress RNA virus: Influenza, 419 HCV, 421 EMCV, 422 435 Coronavirus, 436 Poliovirus, 438 HCV 437 DNA virus: HCMV 488 RNA transcription DNA virus: HPV18, 425,489 HBV, 490 HSV 492 RT virus: HIV 514 RNA polyadenylation RT virus: Rous sarcoma virus 485,486 (HDAC6/8) in the influenza RdRp nuclear import stage. HDAC6/8 inhibitors efficiently limit the polymerase nuclear import and suppress virus replication.…”
Section: Protein Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA virus: YFV 350 Immunity modulation RNA virus: HFDV 354 Cellular transformation DNA virus: HBV, [363][364][365][366] Small chaperone Hsp27 Viral replication RNA virus: EV-A71, 384 Swine fever virus (CSFV), 388 Porcine epidemic diarrhoea virus (PEDV) 389 DNA virus: Adenovirus, 390 HSV-1, 397 Virus entry and uncoating RNA virus: Newcastle disease Virus, 402 DEGV [402][403][404] DNA virus: SV40 413 RT virus: HIV 407,410 Virus translation RNA virus: EV-A71 415 Oxidative stress and ER stress RNA virus: Influenza, 419 HCV, 421 EMCV, 422 435 Coronavirus, 436 Poliovirus, 438 HCV 437 DNA virus: HCMV 488 RNA transcription DNA virus: HPV18, 425,489 HBV, 490 HSV 492 RT virus: HIV 514 RNA polyadenylation RT virus: Rous sarcoma virus 485,486 (HDAC6/8) in the influenza RdRp nuclear import stage. HDAC6/8 inhibitors efficiently limit the polymerase nuclear import and suppress virus replication.…”
Section: Protein Maturationmentioning
confidence: 99%
“…At the transcription level, hnRNP D0B and hnRNP A/B are capable of binding with cis-acting AAGTATGCA core element of HPV18 late promoter to suppress the late genes L1 and L2, which are components of virus capsid proteins. 425,489 hnRNP K binds enhancer II (ENII) to promote HBV replication. Ectopic expression of hnRNP K augments HBV replication; while hnRNP K knockdown significantly decreases HBV viral load.…”
Section: The Function Of Rna Chaperones In Virus Infectionmentioning
confidence: 99%
“…Viral late promoter activation is a key mechanism behind the initiation of late gene expression. The mucosal oncogenic virus late promoters (HPV16 P670 [ 36 ], HPV18 P811 [ 40 ] and HPV31 P742 [ 41 ]) are the best characterized but similarly positioned promoters exist for other HPVs including the cutaneous HPV5 (P840) [ 42 ], and HPV8 (P7535) [ 10 , 43 , 44 ]. The HPV31 late promoter has over 30 possible initiation sites stretching from genome positions 605 to 779 [ 41 , 45 ] while for HPV16, transcription initiation sites have been mapped to various nucleotides within 200 nucleotides surrounding P670 [ 11 , 36 ].…”
Section: Viral Late Promoter Activitymentioning
confidence: 99%
“…The HPV18 late promoter is likely also regulated by similar differentiation-dependent transcription factors but this has not been fully elucidated. A recent intriguing observation is that HPV18 late promoter activity is controlled by the orientation of viral DNA replication, thus providing a clear link between vegetative viral DNA amplification and late transcription [ 40 ]. Moreover, this study revealed that hnRNP proteins A/B and DOB bind a transcriptional repressor to regulate late gene expression.…”
Section: Viral Late Promoter Activitymentioning
confidence: 99%
“…It is interesting to note that the Hnrnpab paralog, AUF1/hnRNP D has been reported to promote transcription of the mTert gene in mouse embryonic fibroblasts, as well as the MEF2C gene during myogenesis, being also shown to promote translation of the MEF2C mRNA in the same cells (Pont et al 2012;Panda et al 2014). Also, both AUF1/hnRNP D and Hnrnpab binding correlate with activity of a transcription repressor element within the late promoter P 811 of the HPV18 virus (Wang et al 2017). Immunolabeling of the Xenopus Hnrnpab ortholog, 40LoVe, in oocytes decorated the actively transcribing lampbrush chromosomes, consistent with association of 40LoVe with chromatin (Czaplinski et al 2005).…”
Section: Hnrnpab Nucleic Acid Binding Is Important For Regulation Of mentioning
confidence: 98%